EVALUASI PENGGUNAAN OBAT DI RUMAH SAKIT MARSUDI WALUYO, KABUPATEN MALANG TAHUN 2016 - Dwi Praetyaning Rahmawati; Fauna Herawati; Susilo Ari Wardani (CALYPTRA, 2018)
Abstract-Optimization of health care has been the major requirement of health care facilities, especially at the era of National health insurance. Optimization of health care presented by the rational, evidence-based, and cost-effective use of medicines that should be evaluated regularly. Evaluation of national formulary application in hospital is part of drug use evaluation, to ensure that patients receive the most evidence-based and cost effective drugs in their medication. Beside of national formulary application evaluation, it also important to evaluate antibiotic consumption, as the prevention of antibiotic resistance, since the resistance of antibiotics influenced by the irrational use of antibiotics. Purpose of this study is to evaluate the application of national formulary, and antibiotics consumption in Marsudi Waluyo Hospital. This study design IS descriptive exploratory retrospective nature. Data were collected from Drug Use Evaluation (EPO) report in 2016. Result of this study showed that suitability percentage between drug use in 2016 and national formulary is 57,04%. Antibiotics consumption calculated by Defined Daily Dose (DDD) 100 patient-days method. Result showed that total value of DDD/100 patient days of those antibiotics is 350,86. The highest DDD value is ofloxacin, i.e: 49,46. The DDD values found in this study indicate a possibility of inappropriate use of antibiotics.